Das Klima und eine marode Infrastruktur richten sich nicht nach der Schuldenbremse - Michael Heine; Hansjörg Herr (Wirtschaftsdienst, 2024)
– The German Federal Constitutional Court has ordered a revision of public budgets following the correct interpretation of the German debt brake. The debt brake is an obstacle to necessary public investment needed for ecological transformation of areas such as housing construction and education. The debt brake should be replaced by the golden rule of fiscal policy, which allows credit financing of public investments.
Keywords: K20; H50; H63; 330; Finanzpolitik; Öffentliche Schulden; Deutschland; Finanzpolitik; Öffentliche Schulden; Deutschland